Deficiencies in Consciousness Studies on Newborns and Animals from Yalçın Koç's Perspective of Transcendence: Transcendence, Language and the Uniqueness of Experience - Baran Bingöl (Felsefe Arkivi)
When one asks and tries to answer any question about newborns and animals, a set of assumptions is found, most of which are implicit. The most important of these involves the fundamental features that make a human being human and that distinguish humans from other living beings. In other words, if one were to have a sharply defined answer to the question of what makes a human being human, this answer would also become the answer to a set of questions about newborns and animals. For instance, if one were to say, “One of the most important features that makes human beings human, or that at least distinguishes humans from other living beings, is language and the ability to learn language,” this statement essentially leads one to assume as an example based on this that a newborn baby and a kitten have both developed as well as not developed language, because development is considered to involve learning or being able to learn a language, and as a result be able to communicate and think using language. The purpose of this paper is to question the fundamental assumptions and starting points (as in the aforementioned example) of studies on consciousness (particularly with regard to newborns and animals), of language, and of philosophy and psychology in general and to offer criticisms and suggestions within the framework of the conception of transcendence as recently developed by Yalçın Koç (Theologia’nın Esasları [The Principles of Theologia]). Finally, this study will address the relationship between having an experience and constructing a system of thought in regard to having an experience in its broadest sense, as well as the possibility of making this a science.